"Stets korrekt und human" Der Umgang der westdeutschen Justiz mit dem NS-Völkermord an den Sinti und Roma - Opfermann, Ulrich Friedrich (Antiziganismusforschung interdisziplinär. Schriftenreihe der Forschungsstelle Antiziganismus, 2023)
This book deals with a neglected area of the judicial reappraisal of the Nazi regime: the handling of the crimes against the Central and Eastern European Roma minority in West German NSG trials. It provides a comprehensive insight and overview, informs about the legal prerequisites of the West German judicial special path, and presents the course of proceedings and the roles of the defendants, witnesses and judicial personnel for a number of proceedings. The focus is on the joint trial on the "Zigeunerkomplex" ("Gypsy Complex", 1958-1970), which was planned as a major trial alongside the first Auschwitz trial and which, contrary to its goal, had little impact and is now forgotten.